Environmental controls of billfish species in the Indian Ocean and implications for their management and conservation. (5th April 2022) - Thoya, Pascal; Kadagi, Nelly Isigi; Wambiji, Nina; Williams, Samuel Mackey; Pepperell, Julian; Möllmann, Christian; Schiele, Kerstin Silke; Maina, Joseph
Abstract: Background and aim: Billfish are epipelagic marine predators facing increasing pressures such as overfishing and rising global temperatures. Overfishing is a major concern, as they are caught by industrial longline fishers targeting tuna. Billfish are targeted by multiple fishing sectors, which provides food, socio‐economic and cultural benefits. To support effective billfish management and conservation, it is essential to understand their spatial distribution and the environmental factors that may influence it. Location: The focus of this study is the Indian Ocean (IO), where there are gaps in understanding the interactions between fisheries and billfish distribution. Three of six billfish species are at risk from overfishing. Therefore, determining their distribution is crucial to their management and conservation. Methods: Using Ocean Biogeographic Information System (OBIS) occurrence data, Indian Ocean Tuna Commission (IOTC) catch data, and environmental covariates, we applied species distribution models to investigate the spatial extent of the realized niches of six billfish species in the IO. We also determined the role and relative importance of environmental drivers. Moreover, we evaluated the association between species' spatial distribution and the fishing effort distribution. Results: We found niche partitioning and overlap among the six species identified spatial distribution, with higher species richness in the northern region of the IO and off the East coast of Africa. Temperature, mixed layer depth and salinity were identified as the most important predictors of species distribution, with moderately warm and stable environments preferred by most billfish species. Areas with high species richness and high fishing effort overlap were primarily found in the Areas Beyond National Jurisdiction (ABNJ). In contrast, areas with high species diversity richness and low fishing effort were found mainly in the Exclusive Economic Zone (EEZ). Main conclusion: Spatial overlap between fishing effort and billfish projected distribution suggests inadvertent fishing pressure on billfish populations as they are caught together with targeted tuna. Spatial distribution transcends maritime zones, reinforcing a need to formulate effective management policies for marine areas beyond national jurisdictions.